A study on the national council of welfare and social development Malaysia : the state of financial reporting of charity organizations / Radiah Othman, Jamaliah Said and Noraini Mohd Nasir - Othman, Radiah; Said, Jamaliah; Mohd Nasir, Noraini (Institute of Research, Development and Commercialization (IRDC), 2006)
In most countries, companies are required to submit their annual financial reports to the relevant authorities. Similarly, some countrIes require charitable organizations to submit their annual reports to the relevant authorities. In Malaysia, all charity organizations, as part of non-profit organizations, have I to be registered with the Registrar ofSocieties (ROS). As part ofthe legal requirement, these organizations must submit their annual reports, including I their financial reports, to the ROS within the stipulated time period. However, less than 50% of the charity organizations do not do so. Thus this study attempts to determine the current state of financial reporting of the charity organizations in the country and highlight major issues and problems faced by them in preparing the financial reports. It is hoped that the findings of this research would assist the relevant authorities andthe organizations themselves to overcome problems related to the non-submission of annual reports as required by the ROS. Annual reports of 32 charity organizations were reviewed for this study and it was found that there were varying degree ofreporting practices among them. All had submitted their balance sheets, but only 60% presented cash flow statement and only 59% had their financial statement auditedby external auditors. Among the problems faced by these organizations in preparing the financial statements were the lack of skilled accounting staff and high staff turnover. These problems may have contributed to the low number ofcharity organizations submitting the annual reports to the ROS.